Penerapan Model Pembelajaran Kooperatif Tipe Team Quiz untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Pada Pelajaran IPA di MI: Team Quiz Cooperative Learning Model, Creative Thinking Ability, Science Subjects - Ramadanti, Nurpauziah; Saefuddin, Asis; Rahman, Alvin Yanuar (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2025)
This study was motivated by the low level of creative thinking skills among fifth-grade students at MI Ar-Rifa in the subject of Natural Sciences. Initial assessment results revealed that out of 24 students, 14 (59%) had not reached the Minimum Mastery Criteria (MMC) of 70, with an average class score of 59.6 and a classical completeness rate of only 41%. The limited development of students’ creative thinking was attributed to the use of conventional teaching models that lacked interactivity and failed to involve students actively in the learning process. This study aimed to explore: (1) the creative thinking abilities of students before the implementation of the Team Quiz cooperative learning model, (2) how the model was applied during the learning process, and (3) the improvement in students’ creative thinking skills after each intervention cycle. Conducted in a fifth-grade classroom at MI Ar-Rifa, the study employed a mixed-method approach, combining qualitative and quantitative data analysis. The research was designed as classroom action research implemented in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through written tests, observation, and documentation. The results indicated a consistent improvement in students’ creative thinking skills. The average score increased from 59.6 in the pre-cycle to 68.5 in the first cycle, and to 75.0 in the second cycle. Likewise, the classical completeness rate rose from 41% to 62% and finally reached 83%. These outcomes demonstrate that the Team Quiz cooperative learning model is effective in enhancing creative thinking skills among students in science learning